Extreme drought boosts CO2 and CH4 emissions from reservoir drawdown areas. Issue 3 (3rd July 2018) - Kosten, Sarian; van den Berg, Sanne; Mendonça, Raquel; Paranaíba, José R.; Roland, Fabio; Sobek, Sebastian; Van Den Hoek, Jamon; Barros, Nathan
ABSTRACT: Although previous studies suggest that greenhouse gas (GHG) emissions from reservoir sediment exposed to the atmosphere during drought may be substantial, this process has not been rigorously quantified. Here we determined carbon dioxide (CO2 ) and methane (CH4 ) emissions from sediment cores exposed to a drying and rewetting cycle. We found a strong temporal variation in GHG emissions with peaks when the sediment was drained (C emissions from permanently wet sediment and drained sediments were, respectively, 251 and 1646 mg m −2 d −1 for CO2 and 0.8 and 547.4 mg m −2 d −1 for CH4 ) and then again during rewetting (C emissions from permanently wet sediment and rewetted sediments were, respectively, 456 and 1725mg m −2 d −1 for CO2 and 1.3 and 3.1 mg m −2 d −1 for CH4 ). To gain insight into the importance of these emissions at a regional scale, we used Landsat satellite imagery to upscale our results to all Brazilian reservoirs. We found that during the extreme drought of 2014–2015, an additional 1299 km 2 of sediment was exposed, resulting in an estimated emission of 8.5 × 10 11 g of CO2 -eq during the first 15 d after the overlying water disappeared and in the first 33 d after rewetting, the same order of magnitude as the year-round GHG emissions of large (∼mean surface water area 454 km 2 ) Brazilian reservoirs, excluding the emissions from the draw-down zone. Our estimate, however, has high uncertainty, with actual emissions likely higher. We therefore argue that the effects of drought on reservoir GHG emissions merits further study, especially because climate models indicate an increase in the frequency of severe droughts in the future. We recommend incorporation of emissions during drying and rewetting into GHG budgets of reservoirs to improve regional GHG emission estimates and to enable comparison between GHG emissions from hydroelectric and other electricity sources. We also emphasize that peak emissions at the onset of drought and the later rewetting should be quantified to obtain reliable emission estimates.